Evaluation of Student Ability through Independent Inorganic Chemistry Practicum Project During Pandemic Period - Nirmalasari, M.A. Yohanita (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Practicum was a subject that was applicable to theory. In inorganic chemistry practicum, students weretrained to apply concepts through independent experiments. This experiment was motivated by severalobstacles, including: difficulty in materials and practicum tools, practicum waste management, and facilitiesavailability. This obstacle was challenged by opportunities in the form of using tools and materials, the usedof digital technology, and the space for student creativity. Therefore, the design of an inorganic practicumwas an independent practicum that starts with preparing a project, did the experiments to communicatingthe output. The research method was objective-oriented evaluative. The research sample was the fifthsemester students of the chemistry education study program, FKIP, Nusa Nipa University. Data collectingwas by interviews, observations, and questionnaires. Data was analysed in descriptively and quantitatively.The results showed that the average ability of students in preparing projects, implementing, andcommunicating practicum results was 87.50%; 83.77% and 89.58%. The average ability was classified asgood, which was indicated by the creativity in creating practicum, using materials in everyday life andutilizing digital technology in creating practical outputs.